1D multi-point marine turbocharger design, for optimal performance recovery. (February 2023) - Ntonas, Konstantinos; Aretakis, Nikolaos; Koskoletos, Orestis A; Mathioudakis, Konstantinos
An integrated turbocharger 1D design tool, allowing retrofit of both compressor and turbine is presented. An optimization procedure is employed, to design both compressor and turbine to match the entire turbocharged system in an optimal way. The optimization process focuses on engine specific fuel consumption reduction in the engine range of operation, while ensuring appropriate matching between turbomachinery components and the diesel engine. Structural integrity of both turbo-components is ensured by using simplified structural and modal analysis. Dimensionless parameters are used as optimization variables, for both compressor and turbine, allowing the design process to become fully automatic. The platform produces four optimal 1D geometries, of different possible centrifugal compressor diffuser and turbine combinations. The combination that gives the best improvement to the diesel engine operation is identified. A case study is presented, where all four turbocharger configurations are designed and analyzed aiming to at least recover the original diesel engine performance. The platform then sorts all four optimized turbocharger geometries based on annual fuel cost reduction. The best configuration achieves the largest fuel consumption reduction (0.4% for the case presented), while stable operation and structural integrity are ensured. Additionally, a study of how the new machine learning volute loss models affect the designed geometry is performed. Finally, a techno-economical assessment is performed in order to identify the most profitable retrofit option, turbocharger redesign being one of four possible turbocharger options considered by the authors. Redesigning the entire turbocharger is shown to provide the largest long term profit.